2001
DOI: 10.1101/gad.883901
|View full text |Cite
|
Sign up to set email alerts
|

The transcription factor FoxH1 (FAST) mediates Nodal signaling during anterior-posterior patterning and node formation in the mouse

Abstract: FoxH1 (FAST) is a transcription factor that mediates

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
156
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 205 publications
(162 citation statements)
references
References 63 publications
(67 reference statements)
5
156
1
Order By: Relevance
“…6B,B′). Gsc and Lefty1 expression in the APS and AVE respectively require high levels of NODAL signalling in the epiblast (Hoodless et al, 2001;Takaoka et al, 2006;Vincent et al, 2003;Yamamoto et al, 2001). We found that Nodal expression was reduced in the epiblast, the primitive streak and the VE of N1ICD epi embryos (n=4/5; Fig.…”
Section: Notch Activation Impairs Axial Mesoderm Formation and Perturmentioning
confidence: 67%
“…6B,B′). Gsc and Lefty1 expression in the APS and AVE respectively require high levels of NODAL signalling in the epiblast (Hoodless et al, 2001;Takaoka et al, 2006;Vincent et al, 2003;Yamamoto et al, 2001). We found that Nodal expression was reduced in the epiblast, the primitive streak and the VE of N1ICD epi embryos (n=4/5; Fig.…”
Section: Notch Activation Impairs Axial Mesoderm Formation and Perturmentioning
confidence: 67%
“…As Cer1 and Leftb are Nodal antagonists, and Drap1 is probably a transcriptional corepressor for Nodal, these defects appear to be a consequence of increased levels of Nodal signaling. In support of this idea, mutant embryos with the loss-of-function of two Nodal signaling modulators, Foxh1 and arkadia (Rnf111 -Mouse Genome Informatics), fail to establish an anterior primitive streak/node and its derivatives (Hoodless et al, 2001;Yamamoto et al, 2001;Episkopou et al, 2001). Finally, either conditional loss-of-function of Smad2, a Nodal effector, in the epiblast or decreased Nodal signals in the primitive streak results in a specific loss of the ADE and prechordal mesoderm (Vincent et al, 2003).…”
Section: Lrp5 and Lrp6 Have Redundant Functions During Embryonic Devementioning
confidence: 86%
“…Fluorescein-, Cy3-and Cy5-conjugated secondary antibodies were obtained from Jackson ImmunoResearch, reconstituted in 50% glycerol according to the manufacturer's recommendation, and used at 1:100, 1:500 and 1:250 dilution, respectively, in the blocking solution. Whole-mount in situ hybridisation was performed by a standard method using digoxigenin-labelled probes 57 . Embryos were staged according to the dissection time (noon of the vaginal plug as E0.5) and morphology.…”
Section: Methodsmentioning
confidence: 99%